FEASIBILITY STUDY ON THE READINESS, BUM DESA KAMPUS KOPI BANYUANYAR AS SOCIAL ENTERPRISE - Ardila, Lina Nur; Hanggana, Sri; Satyanovi, Vidia Ayu; Hapsari, Andi Asri; Hananto, Santosa Tri; Syafiqurrahman, M.; Zoraifi, Renata (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The central government encourages the village government to optimize village potential through Village Owned Enterprises (BUM Desa). Banyuanyar Village isone of the villages that has great potential to be able to develop the local (rural) economy through the management of the BUM Desa business unit. Currently, Banyuanyar Village has been designated by the Boyolali Regent as a pioneer for Tourism Village Kampus Kopi Banyuanyar. The purpose of this study was to identify the readiness of BUM DesaKampus Kopi Banyuanyar as a social enterprise in supporting the improvement of the village economy. The method used for this research is credibility test (triangulation) and SWOT analysis which is adjusted to the internal and external conditions of BUM Desa Kampus Kopi Banyuanyar. The results of the analysis based on priority interests show that in a row are the business environment, quality workforce, access to capital, a good marketing system, and the existence of innovative technology. The business environment is the most important factor in village development. The results of the swot analysis show that the main strength of the aspect of the business environment consists of abundant natural resources, a large population, and not a seasonal type of business. The main weakness in BUM Desa Kopi Banyuanyar Campus is that human resources are not maximized. On external factors there are opportunities and threats. The biggest opportunity of this village is the existence of various natural resources, while the biggest threat is environmental aspects such as the emergence of factories around the village.